Reference architectures: factors for their sustainability - Volpato, Tiago (2018)
Software architectures have played an essential role in determining the quality of software systems. In this scenario, reference architectures is a special type of software architecture that has successfully supported the development, standardization, and evolution of a set of systems. Considering their relevance, many reference architectures are established for diverse domains, such as health, automotive, robotics, and transportation systems. These application domains continually evolve and their reference architectures also need to evolve to continue to be efficient for such domains. However, many of them have not been adequately evolved. Diverse elements, such as design decisions and adherence to good design practices, influence the ability of reference architectures to support continuous changes while maintaining their efficiency; therefore, a major challenge is to ensure the sustainability in reference architectures. Hence, it is quite interesting to be able to analyze the sustainability of these architectures. The main objective of this Masters project is to establish a model concerning factors for analyze sustainability in reference architectures. In order to evaluate our proposal, a survey was conducted with experts to validate such model. 90% of experts agree that the model can be useful to indicate whether a reference architecture is sustainable or not, and 80% of experts think that our model can be useful for building newly sustainable reference architectures.